Species Invasion of Jaguar Cichlid (Parachromis managuensis) in Nyunyur Reservoir - Dadiono, Muh Sulaiman; Murti, Pratiwi Restu; Andayani, Sri (Universitas Tidar, 2024)
Foreign fish, especially predatory fish in Indonesian public waters, are very dangerous for the local ecosystem, foreign predatory fish can become the main predators and can cause an imbalance in the ecosystem. From this study we report the catch of foreign predatory fish from the jaguar cichlid species (Parachromis managuensis) from Central American waters caught in Nyunyur Reservoir, Blitar Regency, East Java. The method in this study used a desk study and jaguar cichlid species identification method using morphological observations based on Kullander and Hartel (1997). This catch is a warning and an important note for the relevant agencies regarding the invasion of the jaguar cichlid species in the Nyunyur Reservoir as an initial step in monitoring aquatic ecosystems.